توظيف المفردات الشعبية في الخزف الكوردستاني المعاصر - عبدالله, نعیمە محمد (Sulaimani Journal for Humanities, 2021)
This research is concerned with studying (employing folk vocabulary in contemporary Kurdish ceramics)، consisting of four chapters: The first chapter includes a presentation of the research problem in questions about (how to employ the vocabulary of folk in contemporary Kurdistan ceramics) and whether the artist or the potter has the ability to employ popular vocabulary and innovate in it، And developing them into new ceramic formations with aesthetic and intellectual ability. While the importance of research and the need for it came through an intensive study to show intellectual vocabulary and decorative units that were used in pottery and folk ceramics، and contemporary artists have benefited from them through their artistic achievements، whether they are directly borrowed or have artistic and aesthetic transformations in the formation of Kurdistan ceramics، and this study enriches The theoretical aspect of the folklore and the folklore in terms of historical، functional and aesthetic terms. The aim of the study is to reveal how the vocabulary of popular use is used in contemporary Kurdish ceramics، while the research sample is determined by studying the ceramic products made in Kurdistan (Sulaymaniyah as a model)، and within the specified time period between (2000-2018). As for the second chapter: it included the theoretical framework، which contained two sections. The first section concerned itself with studying the definition of popular heritage and its historical dimensions in Kurdistan. As for the second topic، it is concerned with studying the employment of popular vocabulary in contemporary formation، and the third chapter deals with the research procedures that included defining the research community. The researcher chose her research sample، as it reached (4) ceramic works by contemporary artists in Kurdistan، intentionally، and then determined the search tool and the method of research، and then Sample analysis. As for the fourth chapter، it includes the results of the research and its conclusions، as well as recommendations.